2021
DOI: 10.1074/jbc.rev120.012411
|View full text |Cite
|
Sign up to set email alerts
|

Using biochemistry and biophysics to extinguish androgen receptor signaling in prostate cancer

Abstract: Castration resistant prostate cancer (CRPC) continues to be androgen receptor (AR) driven. Inhibition of AR signaling in CRPC could be advanced using state-of-the-art biophysical and biochemical techniques. Structural characterization of AR and its complexes by cryo-electron microscopy would advance the development of N-terminal domain (NTD) and ligand-binding domain (LBD) antagonists. The structural basis of AR function is unlikely to be determined by any single structure due to the intrinsic disorder of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 168 publications
(157 reference statements)
0
15
0
Order By: Relevance
“…A variety of mechanisms have been identified that contribute to resistance to novel AR signaling inhibitors, including: AR gain of function point mutations, constitutively active AR transcript variants, AR gene amplification, and most recently, amplifications of an enhancer upstream of the AR gene that regulates AR mRNA expression (2,(11)(12)(13)(14). Furthermore, posttranslational modifications of the AR or changes in AR coactivators also contribute to persistent AR function (15).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of mechanisms have been identified that contribute to resistance to novel AR signaling inhibitors, including: AR gain of function point mutations, constitutively active AR transcript variants, AR gene amplification, and most recently, amplifications of an enhancer upstream of the AR gene that regulates AR mRNA expression (2,(11)(12)(13)(14). Furthermore, posttranslational modifications of the AR or changes in AR coactivators also contribute to persistent AR function (15).…”
Section: Introductionmentioning
confidence: 99%
“…NRF2 binds to and up-regulates the expression of the antioxidant response elements of these genes. This is supported by studies showing that NRF2 inducers elevate AKR1B1 and AKR1B10 expression and that NRF2 signaling is activated by chemicals that produce reactive oxygen species [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 78%
“…Oxidative stress is recognized by nuclear erythroid 2-related factor 2 (NRF2), which binds to the antioxidant response elements of numerous antioxidant/detoxifying genes, including the AKR genes AKR1B1 and AKR1B10, thus upregulating their expression. Studies that support this explanation showed that NRF2 inducers increase AKR1B1 and AKR1B10 expression and that NRF2 signaling is activated by chemicals that produce reactive oxygen species [60][61][62]. The exact mechanism by which an increased AKR1B1 expression is associated with a better survival of patients with HGSC is currently unknown and requires further studies.…”
Section: Discussionmentioning
confidence: 98%